Seniors’ Care System as a Challenge for Local Senior Policy - Richert-Kaźmierska, Anita (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
A significant part of the activities undertaken so far under the senior policy, also at the local level, have been focused on seniors’ social (physical and educational) activation. The growing number of the oldest seniors, with limited independence, living alone in single‑person households, away from their families, will force the policy priorities to be reoriented in such a way as to develop efforts to provide different types of support and care for older citizens. The results of research carried out by different researchers confirm that the system of care for seniors with independence restrictions, based mainly on the family members support, is no longer applicable. However, finding a good solution in new conditions will be extremely difficult. First of all, due to the seniors’ preferences (the desire to spend old age in their own home, in familiar surroundings), social conditions and family relationships (singularization in old age, loosening family and social relationships, transferring social relationships into the virtual sphere inaccessible for many seniors), labor market situation (staff deficit in the care system) and public finances (the need to rationalize the growing public expenditure related to the provision of health and care services). The aim of the article is to present selected aspects of seniors’ care system organization in Poland in local territorial units’ perspective. In the article author presents the results of literature analysis of seniors’ care system in Poland, discusses the results of an interview conducted among the seniors of one of the Pomeranian communes regarding availability of care from the closest family members, as well as proposes the concept of organizing the local care system for seniors.